2018
DOI: 10.1111/pbi.12874
|View full text |Cite
|
Sign up to set email alerts
|

The Ralstonia solanacearum csp22 peptide, but not flagellin‐derived peptides, is perceived by plants from the Solanaceae family

Abstract: Summary Ralstonia solanacearum, the causal agent of bacterial wilt disease, is considered one of the most destructive bacterial pathogens due to its lethality, unusually wide host range, persistence and broad geographical distribution. In spite of the extensive research on plant immunity over the last years, the perception of molecular patterns from R. solanacearum that activate immunity in plants is still poorly understood, which hinders the development of strategies to generate resistance against bacterial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…Our bacterial colonization experiments demon-strate that cellular damage and lateral root emergence does not only unlock MAMP responsiveness to high doses of pure MAMPs such as flg22, or 3-OH-C10:0, but is also effective in unlocking responses to the more complex and probably much less concentrated cocktail of MAMPs associated with actual bacterial colonization. Interestingly, flg22 derived from GMI1000 flagellin was found not to activate the Arabidopsis FLS2 receptor (Pfund et al, 2004;Wei et al, 2018). This indicates that the damage-associated MAMP responses we observe upon GMI1000 infection must be caused by MAMPs other than flg22.…”
Section: Local Gating Of Immune Responses By Damage In Root-bacteria mentioning
confidence: 80%
“…Our bacterial colonization experiments demon-strate that cellular damage and lateral root emergence does not only unlock MAMP responsiveness to high doses of pure MAMPs such as flg22, or 3-OH-C10:0, but is also effective in unlocking responses to the more complex and probably much less concentrated cocktail of MAMPs associated with actual bacterial colonization. Interestingly, flg22 derived from GMI1000 flagellin was found not to activate the Arabidopsis FLS2 receptor (Pfund et al, 2004;Wei et al, 2018). This indicates that the damage-associated MAMP responses we observe upon GMI1000 infection must be caused by MAMPs other than flg22.…”
Section: Local Gating Of Immune Responses By Damage In Root-bacteria mentioning
confidence: 80%
“…This result is in agreement with a parallel study by Wei et al . (), who also identified csp22 as an R. solanacearum PAMP in strain GMI1000, which corresponds to allele 1 (Fig. ).…”
Section: List Of the Core Genes Of The 37 Ralstonia Solanacearum Stramentioning
confidence: 79%
“…2) two csp22 peptides were recognized as PAMPs in either A. thaliana or aubergine, as expected. This result is in agreement with a parallel study by Wei et al (2017), who also identified csp22 as an R. solanacearum PAMP in strain GMI1000, which corresponds to allele 1 (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the control of bacterial wilt is difficult and ineffective due to the high genetic variability, persistence in the environment and broad host range of R. solanacearum. Thus, to discover alternative antimicrobial agents is urgent need [3,8].…”
mentioning
confidence: 99%